Community Partnership Program Peer Educator Benefits Of Cocknut (Vigna Unguiculata) Through The Menopause Home Community In Gunungrejo Village, Singosari Malang - Yuliani, Ita; Sondakh, Jenny JS; Yulindahwati, Asworoningrum (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2023)
Menopausal hypoestrogens cause both physical and psychological complaints. One of the therapies to overcome menopausal complaints is the administration of estrogen hormone replacement therapy (HRT). Peer educator candidates are declared to have passed (from post test scores) and inducted as Peer Educators. Peer Educator passed on knowledge to 30 volunteers (ratio of 1 Peer educator 3 volunteers) and formed Menopause GR home community (own branding) and whatapp group. The knowledge of Peer educator candidates prior to receiving the training was found that half of them had less knowledge about the benefits of cowpea for menopause health, most of them had less knowledge about cowpea buns and half had less knowledge about cowpea milk. After being given Peer Educator training, all of them have good knowledge about the benefits of cowpea for menopausal health; almost all have good knowledge about cowpea dumplings and cowpea milk. Peer Educator passed on knowledge from facilitators to volunteers and the results were obtained. Almost all of them had less knowledge about the benefits of cowpea for menopausal health; most have less knowledge about cowpea dumplings; Almost half had less knowledge about cowpea milk. After being given counseling, almost all volunteers have good knowledge about the benefits of cowpea for menopause health; most have good knowledge about cowpea bakpou and cowpea milk. There is an effect of Peer Educator training on the benefits of cowpeas for menopause health and the manufacture of cowpea dumplings and cowpea milk on menopause knowledge. The results of the Wilcoxon signed ranks test with = 0.05 obtained a p value of 0.025 which is smaller than = 0.05 which means Ha is accepted. So it can be concluded that there is an effect of Peer Educator training on the benefits of cowpea (Vigna Unguiculata) for menopause health on menopause knowledge